Tingkat Resistensi Wereng Batang Coklat (Nilaparvata Lugens) Populasi Kecamatan Lemahabang Karawang Terhadap Insektisida Berbahan Aktif MIPC - Alfarizi, Muhammad Zuhal; Afifah, Lutfi; Adhi, Satriyo Restu; Irfan, Budi (UNIVERSITAS LABUHANBATU, 2023)
Nilaparvata lugens is a major pest of rice in Indonesia which has been established since 1970. The use of synthetic pesticides to treat N.lugens by farmers is considered practical and the results are quickly seen. Continuous application of synthetic insecticides can lead to resistance. This study aims to determine the level of resistance of N. lugens from Lemahabang district, Karawang regency to the insecticide with the active ingredient MIPC. The research method used was an experimental method using a single factor Complete Randomized Design (CRD) with 7 treatments 4 replications consisting of: Control, MIPC 1 g/l, MIPC 2 g/l, MIPC 3 g/l , MIPC 4 g/l , Triflumezopyrim 0.5 ml/l, Azadirachtin 15 ml/l. Tests using N.lugens standard population and field population. The test method uses the IRAC 005 immersion method. The Resistance Ratio (RR) is determined by comparing the LC50 value of the field population with the standard population. The results showed N. lugens in the Lemahabang Subdistrict were still susceptible but there were indications of resistance to MIPC insecticides with RR value of 1.07. Keywords: MIPC,Mortality, Lethal Concentration, Resistance, SusceptibleTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//